2013
DOI: 10.1038/ncomms3235
|View full text |Cite
|
Sign up to set email alerts
|

Genome architecture is a selectable trait that can be maintained by antagonistic pleiotropy

Abstract: Chromosomal rearrangements are mutations contributing to both within and between species variation; however their contribution to fitness is yet to be measured. Here we show that chromosomal rearrangements are pervasive in natural isolates of Schizosaccharomyces pombe and contribute to reproductive isolation. To determine the fitness effects of chromosome structure, we constructed two inversions and eight translocations without changing the coding sequence. We show that chromosomal rearrangements contribute to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 60 publications
3
83
2
1
Order By: Relevance
“…Overall this suggests a common evolutionary history between these strains and species, however an adaptive value of this rearrangement or a case of breakpoint re-usage cannot be ruled out since rearrangements can be adaptive with evidence both from nature and lab setting. (Chang et al 2013; Dunham et al 2002; Avelar et al 2013; Colson et al 2004; Adams et al 1992; Fraser et al 2005; Hewitt et al 2014). Several natural isolates of S. cerevisiae present karyotypic changes (Hou et al 2014) and the reciprocal translocation present between chromosomes VIII and XVI is able to confer sulphite resistance to the yeasts strains in vineyards (Perez-Ortin et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Overall this suggests a common evolutionary history between these strains and species, however an adaptive value of this rearrangement or a case of breakpoint re-usage cannot be ruled out since rearrangements can be adaptive with evidence both from nature and lab setting. (Chang et al 2013; Dunham et al 2002; Avelar et al 2013; Colson et al 2004; Adams et al 1992; Fraser et al 2005; Hewitt et al 2014). Several natural isolates of S. cerevisiae present karyotypic changes (Hou et al 2014) and the reciprocal translocation present between chromosomes VIII and XVI is able to confer sulphite resistance to the yeasts strains in vineyards (Perez-Ortin et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…These isolates have all been termed S. pombe for their phenotypic similarities and the low nucleotide divergence between them, despite the fact that many of these isolates might be significantly reproductively isolated from Sp , just like S. kambucha (Brown et al, 2011; Teresa Avelar et al, 2013). Like the Sk/Sp hybrids assayed in this work, genomic rearrangements are likely the largest contributors to hybrid infertility within other closely related fission yeasts.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being 99.5% identical at the nucleotide level, Sp/Sk hybrids are nearly sterile (Rhind et al, 2011; Zanders et al, 2014); a reproductive barrier between these yeasts must have arisen very recently. This rapid evolution of infertility is common amongst fission yeasts that are generally categorized as isolates of the Schizosaccharomyces pombe species (Avelar et al, 2013). In the case of Sp/Sk hybrids (and likely other pairings), the infertility is caused by both chromosomal rearrangements and multiple meiotic drivers (Zanders et al, 2014; Avelar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This rapid evolution of infertility is common amongst fission yeasts that are generally categorized as isolates of the Schizosaccharomyces pombe species (Avelar et al, 2013). In the case of Sp/Sk hybrids (and likely other pairings), the infertility is caused by both chromosomal rearrangements and multiple meiotic drivers (Zanders et al, 2014; Avelar et al, 2013). Indeed, we previously found that genes on each of the three Sk chromosomes are capable of enacting gamete (spore)-killing meiotic drive against their Sp homologs (Figure 1A) (Zanders et al, 2014).…”
Section: Introductionmentioning
confidence: 99%